Divine proportion of Olympic regattas - Kleshnev, V. (BioRow, 2024)
Did you know that the margins in finals A of World regattas have not changed significantly over the course of more than 30 years? This challenges the common belief that "Olympic competition is getting tougher and tougher these days." This conclusion was made after our latest analysis of margins over the last eight Olympic regattas from 1996 to 2024. The smallest margins were observed at the Olympic regattas in 1996 and 2021, while the largest margins occurred in 2004 and 2008. This 2024 regatta ranks in the median range.